Model Promosi Penjualan dan Citra Perusahaan dalam Pengembangan Loyalitas Nasabah PT Bank Negara Indonesia (Persero) Tbk. Kantor Cabang Utama Tebet - Annisa Milana; Musa Hubeis; Euis Sunarti (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2014)
The commercial banks in Indonesia are currently operating in a more dynamic business environment than before. In the modern competitive environment banks create the value generally using the relational capital. Thus, customer loyalty is the most vital component for bank success in a market. The purpose of the paper is to analyze the effect of sales promotion and corporate image on customer loyalty. To achieve this goal, 80 customers of BNI Taplus account holders of PT BNI (Persero) Tbk. Tebet Main Branch Office were surveyed. Multiple linear regressions technique was used to assess the effect of among the variables under investigation. The findings of this study have shown significant relationships effect of among the sales promotion, corporate image and customer loyalty. Customer loyalty can, therefore, be generated through effective sales promotion and high corporate image.